GLOBAL AND NATIONAL IMPERATIVES FOR THE DEVELOPMENT OF EDUCATIONAL AND PROFESSIONAL POTENTIAL OF INDUSTRY: A COMPARATIVE ANALYSIS - MALTSEV, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article addresses the critical issue of transforming the educational and professional potential of industry under the conditions of the global transition to the Industry 5.0 paradigm and the specific challenges of Ukraine's post-war recovery. The study aims to identify key trends and compare adaptation strategies of developed countries with the Ukrainian experience in preserving and developing human capital. The methodological basis of the research includes a comparative analysis of statistical data from Eurostat and the State Statistics Service of Ukraine, as well as a systematic review of structural changes in the labor market.The research reveals a fundamental difference in human capital challenges. It is established that for the EU, the development of industrial potential is an evolutionary process focused on adapting to an aging population and gradual digitalization. In contrast, Ukraine faces an existential crisis characterized by a "double shock": the urgent need for integration into high-tech value chains combined with unprecedented losses of labor resources and educational infrastructure due to the full-scale war. The paper highlights a paradox in the Ukrainian context: despite a significant number of STEM graduates, there is a qualitative gap between theoretical training and the practical needs of the modern high-tech industry, exacerbated by massive external migration of qualified personnel.The author proposes a matrix of professional demand transformation in Ukraine's industrial specialization forecast up to 2030. The study identifies priority "High Demand" zones, which include recovery engineering and construction, military engineering (Defense Tech), and green energy technologies. The findings demonstrate that due to the institutional inertia of the traditional state education system, the corporate sector is becoming the main architect of educational and professional potential. Ukrainian business is actively adopting functions of professional training through the expansion of corporate universities, the implementation of dual education models, and the use of micro-qualifications for rapid re-skilling of veterans and internally displaced persons. The article concludes that the successful restoration of Ukraine's industrial potential requires not extensive growth, but a radical qualitative transformation: full synchronization of the national qualifications framework with EU standards, legalization of micro-credentials, and a shift in focus towards practical application of STEM education to ensure the resilience of the national economy.
Keywords: educational and professional potential; human capital; STEM education; labor market; post-war recovery; dual education; professional training; micro-credentials